Ո՛չ միայն հացիւ... - Սարիբեկեան, Էլեա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена просветительской, церковно-строительной и издательской деятельности, осуществлявшейся при Католикосе Всех Армян Гарегине II, вклад которого в указанные области велик. Благодаря Его Святейшеству наряду с Первопрестольным Святым Эчмиадзином были отреставрированы и возведены тысячи церквей и монастырей по всей Армении и Арцаху. Благодаря усилиям Католикоса Всех Армян также получила новый импульс типографика, развивались межцерковные отношения и епархиальные структуры, а в школах был введен предмет «История Армянской Церкви». The article is devoted to educational, church-building and publishing activities carried out during the reign of the Catholicos of All Armenians Karekin II. His contribution to these areas is great. Thanks to him, hundreds of restored and newly built churches and monasteries stand next to the Mother See of Holy Etchmiadzin throughout Armenia and Artsakh. By virtue of his efforts, typography received a new impetus, interchurch relations and diocesan structures developed, and the subject “History of the Armenian Church” was introduced in schools as a separate subject.
Keywords: Հայոց պատմութիւն; Հայոց եկեղեցի